A tryptophan-containing fluorescent intramolecular complex as a designer peptidic proton sensor. Issue 22 (19th May 2016) - Haridas, V.; Yadav, Anita; Sharma, Sakshi; Pandey, Siddharth
Abstract : Pyrene and tryptophan groups judiciously placed on a molecular scaffold, namely, bispidine exhibited fluorescence due to the formation of an emissive intramolecular complex. Abstract : Pyrene and tryptophan groups judiciously placed on a novel molecular scaffold, namely, bispidine exhibited fluorescence due to the formation of an unprecedented emissive intramolecular complex in polar solvents. Upon protonation, the emission signal from the pyrene unit enhances at the expense of the emission signal from the complex. The probe demonstrates good sensitivity, excellent selectivity, and adequate reversibility towards proton sensing. The present design based on the bispidine scaffold opens up newer opportunities for the design of novel bispidine-peptide sensors.